2005
DOI: 10.1177/0886260504270334
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the New Context of the Male Sex Work Industry

Abstract: The article reviews past and recent research on male sex work to offer a context to understand violence in the industry. It provides a critical review of research to show, first, the assumptions made about male sex workers and violence and, second, how such discourses have shaped thinking on the topic. The article presents a case study and original findings from two studies conducted by the authors in Australia and Argentina on violence in the male sex industry. Finally, the article reviews examples of legisla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 20 publications
0
64
0
2
Order By: Relevance
“…Notwithstanding the heterogeneity of male sex workers, some common characteristics are frequently detected among them, such as poor education, disrupted upbringings, low socioeconomic level, large number of sexual partners, unsafe sexual relations, alcohol and drug misuse, and history of criminal activities (Brannigan & Van Brunschot, 1997;Caukins & Coombs, 1976;Sausa, Keatley, & Operario, 2007;Scott et al, 2005;Timpson, Ross, Williams, & Atkinson, 2007). Also, comparing the group of male with female sex workers, the former seems to be more exposed to risky sex behaviors than the latter (Belza, 2005;Dandona et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Notwithstanding the heterogeneity of male sex workers, some common characteristics are frequently detected among them, such as poor education, disrupted upbringings, low socioeconomic level, large number of sexual partners, unsafe sexual relations, alcohol and drug misuse, and history of criminal activities (Brannigan & Van Brunschot, 1997;Caukins & Coombs, 1976;Sausa, Keatley, & Operario, 2007;Scott et al, 2005;Timpson, Ross, Williams, & Atkinson, 2007). Also, comparing the group of male with female sex workers, the former seems to be more exposed to risky sex behaviors than the latter (Belza, 2005;Dandona et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Somewhat surprisingly, we found that there is little high quality epidemiological data, a fact that has also been highlighted in review articles on this issue. [20][21][22] Indeed, and much like the overall male sex work literature, much of the available data on male sex work in South-east Asia is derived from brief and relatively limited surveillance studies of cognate risk populations in which male sex work is also prevalent (particularly IDU). In most cases, these studies use a sampling approach and assessment measures that are not well suited to assessing the social, economic and behavioural complexity of male sex work itself, a fact that we fully acknowledge is also a limitation of the study from which this data is derived.…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (46) note that violence associated with male sex workers tends to be associated with setting and client characteristics more than with the male sex worker. Variables that tend to be associated with violence against sex workers include sex role (masculine or feminine), and the services offered: the degree to which male sex workers are at risk is tempered by characteristics such as age, social class, and ethnicity.…”
Section: Male Sex Workersmentioning
confidence: 99%